Parent selection for hybridization in chilli (Capsicum annuum L.) using multivariate analysis and K-means clustering - Sharmeen, Farhana; Saikat, Mohammad Mehfuz Hasan; Ahmed, Jalal Uddin; Islam, Md Tofazzal; Islam, A K M Aminul (Fundamental and Applied Agriculture, 2022)
The study was conducted to elucidate the phenotypic variability and extent of genetic diversity of 28 chilli (Capsicum annuum L.) genotypes. The selected chilli genotypes were grown at the Field Laboratory of the Department of Genetics and Plant Breeding of Bangbandhu Sheikh Mujibur Rahman Agri- cultural University, Bangladesh with recommended agronomic practices. The experiment was laid out in a randomized complete block design with tree replications. The analysis of variance revealed considerable variability among the genotypes for the character studied. Genetic diversity in chilli genotypes were estimated based on 16 growth and yield contributing charac- ters using Mahalanobis’s D2 statistics and K-means clustering. The genotypes were grouped into four different clusters by non-hierarchical clustering. Clus- ter III had the maximum number (13) of genotypes followed by cluster I, IV and II with 7, 5 and 3 genotypes, respectively. The highest inter-cluster ge- netic divergence (9.87) was recorded between clusters II and IV, whereas the highest intra-cluster distance was recorded in cluster II (4.37). Cluster II was observed to be the most important with maximum cluster means for most of the valuable traits including number of fruits per plant and number of fruit yield per plant. The characters fruit yield/plant, days to 100% fruiting, days to first flowering and individual fruit weight contributed maximum towards divergence. Considering diversity pattern and other horticultural performance the Genotype7 and Genotype20 from cluster I, Genotype8 and Genotype 10 from cluster IV and Genotype24 from cluster III may be taken into consideration as better parents for an efficient hybridization program of chilli.